2018
DOI: 10.1038/s41467-018-03128-9
|View full text |Cite
|
Sign up to set email alerts
|

Human Semaphorin-4A drives Th2 responses by binding to receptor ILT-4

Abstract: Semaphorin-4A (Sema4A) has been implicated in the co-stimulation of T cells and drives Th1 immune responses by binding to the receptor T-cell immunoglobulin and mucin domain protein 2 (Tim-2) in mice. Here we show that human, but not murine, Sema4A is preferentially expressed on antigen-presenting cells, and co-stimulates CD4+ T-cell proliferation and drives Th2 responses. By employing two independent cloning strategies, we demonstrate that Immunoglobulin-like transcript 4 (ILT-4) is a receptor for human SEMA4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 49 publications
6
70
2
Order By: Relevance
“…In this study we directly demonstrated a requisite role for Sema4A in the production of Th17, but not Th1 or Th2 cytokines, by human CD4+ T cells. In contrast with our observation, Sema4A was recently reported to induce proliferation and Th2 polarization in human CD4+ T cells . These differences may be attributed to the different recombinant Sema4A protein used, the different manner of CD4+ T cell activation and proliferation, and the use of CD4+ T cells from adult blood buffy coats.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study we directly demonstrated a requisite role for Sema4A in the production of Th17, but not Th1 or Th2 cytokines, by human CD4+ T cells. In contrast with our observation, Sema4A was recently reported to induce proliferation and Th2 polarization in human CD4+ T cells . These differences may be attributed to the different recombinant Sema4A protein used, the different manner of CD4+ T cell activation and proliferation, and the use of CD4+ T cells from adult blood buffy coats.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results show that all 3 of these receptors are involved in Sema4A signaling in CD4+ T cells, although the highest inhibition of Sema4A‐induced Th17 cytokine production was observed after the blocking of plexin D1. This finding might be explained simply by the fact that the percentage of CD4+ T cells expressing plexin D1 is much higher than those expressing plexin B2 and NRP‐1, but we cannot rule out the potential differential blocking efficiency of antibodies used, residual expression of plexin B2 following gene silencing, or involvement of immunoglobulin‐like transcript 4, a recently identified Sema4A receptor in CD4+ T cells .…”
Section: Discussionmentioning
confidence: 86%
“…The role of Plexin B1 in CD4 + T cell differentiation and function has not been examined before, to our knowledge. Moreover, a novel Sema4A receptor Ig-like transcript 4 (ILT-4) has been recently cloned, and its functional activity on CD4 + T cells has been examined (58). Naive CD4 + T cells were cocultured with hSema4A-expressing L cells in the presence of T cell-activating factors, immobilized anti-CD3 and anti-CD28 Abs, or under Th1-or Th2-skewing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…4d, e). Recently, Lu et al reported that human Sema4A regulate Th2 differentiation [17]. We analyzed IL-4 level in the sera and GATA3 expression in CD4+ T cells in RRMS patients.…”
Section: Rrms Patients With High Sema4a Levels Present Th17 But Not Tmentioning
confidence: 95%